Chemical characteristics of soil after application of tannery sludge as fertilizer in the sugarcane plant crop - Santos, Alessandro José Marques; Backes, Clarice; Rodrigues, Lucas Matheus; Teodoro, Arthur Gabriel; de Godoy, Leandro José Grava [UNESP]; Tomazello, Danilo Augusto; Campos, Luiz Fernandes Cardoso; Ribon, Adriana Aparecida; Lopes, Tatiany Arrais; Boas, Roberto Lyra Villas [UNESP] (Southern Cross Publishing, 2020)
The aim of this study was to examine the effects of applying tannery sludge as fertilizer in the sugarcane plant crop and its impact on soil chemical characteristics. The soil in the experimental area was classified as dystrophic red latosol type (Oxisol). The experiment was set up as a randomized-block design with four replicates, with treatments represented by five doses of tannery sludge (0, 4500, 9000, 13500 and 18000 kg ha-1) plus one treatment with inorganic fertilization (90 kg ha-1 N, 180 kg ha-1 P2O5 and 120 kg ha-1 K2O). Soil chemical characteristics and sugarcane nutrition and production traits were evaluated. Tannery sludge application increased the organic matter, Ca, S and Na contents in the soil layers of 0-0.20 and 0.20-0.40 m. Heavy metal contents in the soil were not influenced by the treatments. Tannery sludge showed the potential to supply important macronutrients, especially at the highest doses tested. Tannery sludge doses between 10000 and 16250 kg ha-1 provided the greatest plant height and diameter and the highest number of stalks. The highest sugarcane yield, 149.55 t ha-1, was obtained with the sludge dose of 18000 kg ha-1.
Keywords: Industrial waste; Nitrogen; Plant nutrition; Recycling; Saccharum officinarum